The Costume and Properties of the Kedidi Dance in the Perang Ketupat Traditional Ceremony - Ananda Sagina Pratama; Rio Eka Putra; Nofroza Yelli (Edumaspul: Jurnal Pendidikan, 2026)
This study aims to describe and analyze the costume and props of the Kedidi Dance in the Perang Ketupat Traditional Ceremony, developed by the Limaupurut Studio. The Kedidi Dance is a traditional dance that has grown and developed within the community as a medium for cultural expression and a means of preserving local values. Costume and props are important elements in dance performances because they play a role in strengthening the character, symbolic meaning, and aesthetic value of the performance. However, studies that discuss these two elements in depth are still limited, so this study focuses on revealing the form, function, and meaning contained within them. The method used in this study is a qualitative method with a descriptive approach. Data collection was carried out through observation, interviews, and documentation. The data obtained were then analyzed through the stages of data reduction, data presentation, and conclusion drawing to obtain a comprehensive picture of the costume and props of the Kedidi Dance. The research results show that the Kedidi Dance’s costume and props are adapted to the dance’s character and Bangka Belitung’s cultural identity. Furthermore, the props used serve not only as visual support but also as symbols that reinforce the meaning of the dance’s movements and concepts. The findings of this study contribute to arts education, particularly dance education, as a reference and learning resource regarding the supporting elements of traditional dance. This research is expected to support efforts to preserve regional arts and culture and serve as a reference in the development of dance instruction in schools and studios.